EXAMINATION IN AUDITING. - Meigs, Walter B. (The Accounting Review, 1961)
The article presents information on examinations in auditing with special reference to one of the problems that was included in the question paper. The auditing section of the May 1961 Uniform C.P.A. Examination was given on May 18, 1961. It is assumed that the amounts involved at the western outlet are material if these items were not material there would be no necessity for any audit work. The principal auditor should be willing to accept full responsibility for the work of another auditor under the following conditions: the other auditor is selected by the principal auditor after appropriate inquiry and investigation. The other auditor is a correspondent firm previously used with satisfactory results by the principle auditor. If the client acted on his own initiative to retain the other auditor, the principle auditor may not wish to accept responsibility for that phase of the work and should disclose in the audit report the use of other independent accountants for examination of the western outlet.